Evaluasi Status Kesuburan Tanah Pada Penggunaan Lahan Sawah di Subak Kecamatan Denpasar Utara Berbasis Sistem Informasi Geografis (SIG) - Risky Novelin Simatupang; Ni Made Trigunasih; I Dewa Made Arthagama (Fakultas Pertanian, Universitas Udayana, 2021)
This study aims to determine the status of soil fertility in subak land, North Denpasar District, to determine the limiting factors, and to provide direction on soil fertility management actions. This research was conducted by field survey method and soil test method carried out in the Laboratory of Soil and Environmental Sciences, Faculty of Agriculture, Udayana University. The chemical properties analyzed were Cation Exchange Capacity (CEC), Base Saturation (BS), P-total, K-total, and C-organic. The results showed that soil fertility in North Denpasar District there are two soil fertility statuses, namely high fertility status (T) in SLH I (Subak Sembung and Subak Pakel I), II (Subak Lungatad and Subak Kedua), and IV (Subak Petangan and Subak Subak Ubung) and medium fertility status (S) in SLH III (Subak Pakel II and Subak Dalem). The limiting factor is the low P-total value. Based on the results of the study, it can be suggested land management by adding fertilizers containing P in the form of single fertilizer or compound fertilizers.